Empréstimos relacionados com a cosmética e o tratamento do corpo no léxico português (Philology, 2019)
The present study intends to put an emphasis on introducing loanwords in the Portuguese language, as well as to present some problems related to the use of loanwords related to body treatment in the Portuguese lexicon. Taking into account the work of several Portuguese and Brazilian linguists, we intend to see loanwords as an enriching element; however, their exaggerated use may cause some doubts and lead to incomprehension.There are also several examples found in women’s blogs. Assuming that each language needs to renew its lexical assets to function as a communication tool due to the appearance of new objects and phenomena, a loanword is one of the very important elements of this process, and the needs of each language are an indispensable criterion in introducing foreign words in the domain of cosmetics.
Keywords: loanwords; Anglicism; foreign words; blog; Portuguese; Internet